Legal Protection for Women in Employment Contracts and Entrepreneurship: A Review of Gender Economic Justice (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to analyze legal protection for women in work contracts and entrepreneurship. The research method used in this research is the normative juridical method. The data used in this research is secondary data from relevant sources and relevant legal sources. The results of this research describe a series of legal and policy efforts aimed at protecting women's rights in the workplace so that there are legal guarantees for women in economic terms. First, Law no. 13 of 2003 concerning employment regulates various aspects of protection, such as special working hours and leave rights related to pregnancy and childbirth. Second, Law no. 7 of 1984 emphasizes equal pay for all genders of workers, avoiding wage discrimination based on gender. Third, Law no. 39 of 1999 concerning Human Rights highlights the protection of women's rights, including the right to work and a decent income. Fourth, Law no. 23 of 2004 concerning the elimination of domestic violence stipulates the protection of women from various forms of violence, including at home and in the workplace. Fifth, Government Regulation no. 78 of 2015 stipulates equality in setting minimum wages, avoiding discrimination based on gender. Lastly, Minister of Manpower Regulation no. 18 of 2022 sets sectoral minimum wages by taking into account the special needs of women, demonstrating a commitment to creating an inclusive and fair work environment.